PRAGMATIC DISORDER AND COMMUNICATION STRATEGIES OF MENTAL RETARDATION CHARACTER IN I AM SAM MOVIE - Zahirah, Ulfatuz; Indah, Rohmani Nur (Annual International Conferences on Language, Literature, and Media, 2023)
Many experts have investigated the issues regarding language disorders in mental retardation since it affects the communication process. However, little is known about pragmatic disorders in people with mental retardation. This study aims to analyze the main character's pragmatic disorder and communication strategies with mental retardation in the I Am Sam movie. It is based on John Carroll’s (1985) and Hatton's theory (1998). The researcher observed Sam as the main character with mental retardation. She used a descriptive qualitative method to deeply understand the pragmatic disorders in the main character's mental retardation. The findings of this study indicated that of the seventeen utterances produced by Sam, the researcher found four out of eleven types of language disorders using John Carroll’s (1985) theory and three out of four types of pragmatic disorders using Hatton’s (1998) theory. The types of language disorders found are: having difficulty finding words; not appearing to listen; having difficulty understanding complex sentences; and showing a lack of interest. In conclusion, this research established that mentally retarded people have expressive and receptive language disorders caused by low intelligence. Furthermore, this study discovered three communication strategies to cope with the pragmatic disorder: using more submissive and indirect conversational strategies with their peers without disabilities, using more dominant conversational strategies with their disabled peers, and using sophisticated pragmatic language only rarely.